Siddhartha - Hesse, Hermann, 1877-1962 (1971)
The story concerns a young Brahman who quits his comfortable home to join a roving group of holy men in striving to empty their hearts of passion and desire through self-denial and meditation.
1010
Accelerated Reader AR
Keywords: Gautama Buddha -- Fiction; Authors, German -- 20th century; Buddha and Buddhism -- Fiction; India -- Fiction